Analysis of eclipsing binaries in multiple stellar systems: the case of V1200 Centauri. Issue 2 (2nd October 2020) - Marcadon, F; Hełminiak, K G; Marques, J P; Pawłaszek, R; Sybilski, P; Kozłowski, S K; Ratajczak, M; Konacki, M
ABSTRACT: We present a new analysis of the multiple-star V1200 Centauri based on the most recent observations for this system. We used the photometric observations from the Solaris network and the Transiting Exoplanet Survey Satellite telescope, combined with the new radial velocities from the CHIRON spectrograph and those published in the literature. We confirmed that V1200 Cen consists of a 2.5-d eclipsing binary orbited by a third body. We derived the parameters of the eclipsing components, which are M_ Aa = 1.393± 0.018 M⊙, R_ Aa = 1.407± 0.014 R⊙, and T_eff, Aa = 6588± 58 K for the primary, and M_ Ab = 0.8633± 0.0081 M⊙, R_ Ab = 1.154± 0.014 R⊙, and T_eff, Ab = 4475± 68 K for the secondary. Regarding the third body, we obtained significantly different results than those previously published. The period of the outer orbit is found to be 180.4 d, implying a minimum mass of M_ B = 0.871± 0.020 M⊙ . Thus, we argue that V1200 Cen is a quadruple system with a secondary pair composed of two low-mass stars. Finally, we determined the ages of each eclipsing component using two evolution codes, namely mesa and cestam . We obtained ages of 16–18.5 and 5.5–7 Myr for the primary and the secondary, respectively. In particular, the secondary appears larger and hotter than that predicted at the age of the primary. We concluded that dynamical and tidal interactions occurring in multiples may alter the stellar properties and explain the apparent non-coevality of V1200 Centauri.